Dampak Profesionalisme Kerja Pegawai terhadap Pelayanan Masyarakat di Kelurahan Teddaopu Kecamatan Tempe Kabupaten Wajo - Qadar, Jamal; Supriadi, Andi (JURNAL EKOLOGI BIROKRASI, 2022)
The study aims to determine the excellent professionalism of employees and community service and to see how much influence employee professionalism has on community service in the Teddaopu Village Office, Tempe District, Wajo Regency, using a descriptive associative census research type with a quantitative. Approach the results of this study to indicate that employee professionalism positively affects community service at the Teddaopu Village Office, Tempe District, Wajo District, which is reflected in the employee professionals variable with an average acquisition score of 84,87% and this is in a good category. While the community service variable with an average acquisition score of 83,38% is in a good category.